Preparation method of methyl modified polyaniline and construction of supercapacitor with excellent cycle stability
By introducing methyl functional groups and hydrogen bonding agents into polyaniline, a dynamic self-healing electrode material is formed, which solves the problem of structural damage in PANI during electrochemical cycles and improves the cycling stability and capacity of the supercapacitor.
Patent Information
- Application Number
- CN202411897798.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Polyaniline (PANI) causes structural damage due to volume expansion/contraction during the electrochemical charge and discharge cycle, resulting in poor circulation stability.
By introducing methyl functional groups into the aniline derivatives, the flexibility and chain spacing of the polymer chain are adjusted, and combined with hydrogen bonding agents are combined to form a dynamic self-healing electrode material to stabilize the electrode structure.
The cyclic stability and capacity of the polyaniline-based supercapacitor is improved, the self-healing of the electrode structure is achieved, and the electrochemical cycle life is extended.
Smart Images

Figure CN119708473A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical energy storage, and specifically relates to a preparation method of methyl-modified polyaniline and the construction of a supercapacitor with excellent cycle stability. Background Art
[0002] With the continuous advancement of modern science and technology, the increasingly prominent energy consumption and shortage issues have gradually become a social hot spot. In the past few decades, the use of fuel cells, chemical batteries, and capacitors has alleviated the pressure of energy consumption to a certain extent, but the high production cost, limited equipment life, and environmental unfriendliness have always restricted the further development of the energy industry. Supercapacitors, as an energy storage device between secondary batteries and traditional capacitors, have considerable advantages in rate performance, charge and discharge rate, cycle life, and cost of use, making them a very potential energy storage device in the development of new energy.
[0003] PANI has the advantages of high theoretical specific capacity, good stability, environmental friendliness and low cost. It is used in electrochemistry, electrochromism, anti-corrosion coatings and many other fields. However, due to the insertion / extraction of ions during the electrochemical charge and discharge cycle of PANI, the conjugated rigid structure of PANI will be accompanied by volume expansion / contraction, resulting in the powderization of the material and damage to the electrode structure. Therefore, some electrode materials cannot participate in electronic contact, resulting in PANI capacity decay and poor cycle stability. Introducing functional groups into the benzene ring of the PANI molecular chain is one of the methods to adjust the distance between PANI molecular chains and the conjugation effect of the benzene ring. Methyl, as a weak power supply group, appropriately reduces the conjugation effect of the benzene ring while ensuring its electrochemical activity, making the molecular chain softer, adjusting the PANI morphology, and making PANI have a higher specific capacity. The self-healing process can be designed by adding functional guest materials inside or on the top of the polymer matrix in the composite system. The bond reorganization can occur between two polymer chains, between two or more different polymers, or between polymer chains and other guest small molecules or nanomaterials. Therefore, in order to achieve the restoration of its electrode structure and restore its capacity, it is necessary to design a self-healing electrode material with wide applicability. According to the self-repair mechanism, the kinetics of the formation of dynamic covalent bonds such as Diels-Alder reaction, disulfide bonds, and imine bonds are slow, and often require external stimulation, such as heating, pH response, etc. to trigger the healing process, and the actual application conditions are relatively harsh. Non-dynamic covalent bonds, mainly hydrogen bonds, can realize dynamic self-healing processes at room temperature. With the power of supramolecular self-assembly and the fluidity of polymer chains, the healing process can be greatly shortened. In this context, the method of using methyl-modified polyaniline and hydrogen-bonded binders can be actually applied to the performance improvement of polyaniline-based supercapacitors, and is expected to meet many practical application environments. Summary of the invention
[0004] In view of the shortcomings of the above-mentioned prior art, the present invention provides a method for preparing methyl-modified polyaniline and the construction of a supercapacitor with excellent cycle stability. The present invention is based on the structural damage caused by the volume expansion of PANI during the charge and discharge cycle, and adjusts the flexibility and chain spacing of the polymer chain by copolymerizing aniline derivatives, combined with the traction effect of hydrogen bonds on electrode materials, and introduces a hydrogen bond binder containing a large number of hydrogen bonds, so that the methyl modification combined with the hydrogen bond binder promotes the stability of the electrode structure, and provides a simple and effective method for improving the capacity and electrochemical cycle life of polyaniline-based supercapacitors.
[0005] The present invention uses N-phenyl-p-phenylenediamine (AD) and m-methylaniline (mT) to copolymerize, introduce methyl functional groups on the benzene ring, weaken the intermolecular forces of the polymer, and regulate the morphology of polyaniline. That is, the present invention regulates the morphology of polyaniline by introducing methyl functional groups between aniline dimers and benzene rings, improves its capacity and further combines it with self-healing materials, uses the abundant hydrogen bonds in amide bonds to repair the structural damage of polyaniline during the cycle, stabilizes the electrode structure, and enhances the cycle stability and capacity of polyaniline-based supercapacitors.
[0006] The preparation method of methyl modified polyaniline of the present invention comprises the following steps:
[0007] Step 1: Weigh 100-500 mg N-phenyl-p-phenylenediamine (AD), add it into a mixed solution of 5-20 mL ethanol and 10-30 mL 1M HCl, stir evenly, and disperse it by ultrasonic for 10-30 min, which is recorded as solution A;
[0008] Step 2: Weigh 100-500 mg of m-methylaniline (mT), add 10-50 mL of 1 M HCl, stir evenly, and disperse by ultrasound for 10-30 min, which is recorded as solution B;
[0009] Step 3: Weigh 300-1500 mg APS, add 20-80 mL 1 M HCl, stir evenly, and place at 0-5°C for 10-50 min, which is called solution C;
[0010] Step 4: Pour the solution B obtained in step 2 into the solution A obtained in step 1, disperse by ultrasonic at 0-5°C for 10-30min, and then stir at 0-5°C for 10-40min;
[0011] Step 5: Slowly drip the solution C obtained in step 3 into the system of step 4 with stirring, the dripping rate is 1-5s / drop, the dripping process is maintained for 0.5-2h, and the reaction is continued with stirring at 0-5°C for 4-12h.
[0012] Step 6: The reaction solution obtained in step 5 is washed by centrifugation with a mixed solution of deionized water and ethanol to remove residual acid and organic matter, and the product is collected by freeze drying to obtain methyl-modified polyaniline, which is recorded as PACM.
[0013] The present invention also provides a method for constructing a supercapacitor with excellent cycle stability, which uses the PACM or PANI as an active material, SIR as a hydrogen bond binder, conductive carbon black (SP) as a conductive agent, polybenzimidazole (PBI) as a binder, and N-methylpyrrolidone (NMP) as a solvent to prepare an electrode slurry, and uses graphite paper as a current collector to coat the slurry to prepare an electrode; at the same time, PBI is used as a diaphragm and H3PO4 is used as an electrolyte; the two electrode sheets are coated with active material on one side facing each other, and are stacked together with the diaphragm in a sandwich structure, and the sides loaded with active material are respectively bonded to the middle PBI film to assemble into a symmetrical device.
[0014] During the preparation of symmetrical device slurry, the mass ratio of PACM or PANI, SIR, SP and PBI is (70%-97%): (1%-15%): (1%-15%): (1%-10%). Graphite paper (GP) is used as the current collector, and the slurry coating area is >1cm 2 .
[0015] The concentration of the electrolyte is 1M-6M.
[0016] The loading mass of active material per electrode is 0.1-5 mg / cm 2 The loading mass of the device active material is 0.2-10mg / cm 2 .
[0017] The active material PANI synthesis method is as follows:
[0018] Take a certain amount of aniline (An) monomer and evenly disperse it in 1M HCl solution, which is solution I; weigh a certain amount of ammonium persulfate (APS) and ultrasonically disperse it in an equal volume of 1M hydrochloric acid solution, marked as solution II; slowly add solution II to solution I in an ice bath, stir magnetically, the addition time is 30 minutes, and the reaction time is 4-8 hours. Centrifuge and wash, wash with deionized water and ethanol 3-4 times until the centrifuge is neutral, and collect the product. The molar ratio of aniline (An) monomer to ammonium persulfate (APS) is 1:1.
[0019] The synthesis method of the hydrogen bonding agent SIR is as follows:
[0020] (1) Take 100-500 mL of isophorone diisocyanate (IPDI) in a three-necked flask, add 1-10 mL of dimethylformamide (DMF), stir evenly, and mark it as solution X;
[0021] (2) Weigh 0.2-5 g of poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (Pluronic P123), add 0.1-10 mg of dibutyltin dilaurate (DBTDL) and 1-20 mL of dimethylformamide (DMF), stir well, and record as solution Y;
[0022] (3) Weigh 100-700 mg of imidazolidinyl urea (IU), add 1-20 mL of dimethylformamide (DMF) and stir evenly, marking it as solution Z;
[0023] (4) Pour solution Y into solution X, place the three-necked flask in an oil bath with magnetic stirring, and then heat at 60-100°C for 4-8 hours. After heating, add solution Z to the three-necked flask and continue to slowly heat and stir for 8-16 hours.
[0024] (5) After the reaction is completed, 50-300 mL of isopropyl ether (IPE) is added to the product to produce a precipitate, and the precipitate is collected by centrifugation. The precipitation-centrifugation operation is repeated twice, and the collected precipitate is placed in a 60°C vacuum drying oven to dry for 12-24 hours, and 5-30 mL of NMP is added to dissolve the precipitate to prepare a SIR solution with a concentration of 10-50 wt%. Since the electrode slurry uses NMP solvent, the fact that SIR can be dissolved in NMP is more convenient for electrode preparation.
[0025] Preparation method of PBI solution: weigh 1-5g PBI powder, add it to 20-100mL dimethylacetamide (DMAC) solution, heat and stir at 120°C for 4-6h, take out and cool, and obtain 1-10wt% PBI solution.
[0026] Preparation method of PBI membrane: Take a PBI solution with a mass concentration of 1-10wt% (typical value is 5wt%) and spread it evenly on a flat glass plate, slowly shake it to make the liquid level, and dry it at 60°C for 8-12h to obtain a PBI membrane with a film thickness of 10-30μm.
[0027] Three-electrode tests were carried out on PACM electrodes synthesized with different monomer mass ratios, and the electrochemical performance of symmetrical devices with different SIR addition amounts was tested.
[0028] The present invention conducts electrochemical performance testing under a pressure of 0.01-5 MPa.
[0029] The beneficial effects of the present invention are embodied in:
[0030] 1. The raw materials used are easy to obtain, low cost, green and environmentally friendly, and have low instrument requirements and simple operation.
[0031] 2. The present invention regulates the intermolecular forces of polyaniline by substituting the meta-methyl group on the benzene ring, thereby improving the morphology of polyaniline and increasing the specific capacity of the material, improving the electrochemical properties of polyaniline, and also providing a solution for regulating the performance of polyaniline in terms of monomer copolymerization.
[0032] 3. The present invention uses a relatively simple method to introduce a hydrogen-bonded binder into a supercapacitor device to prepare a self-healing polyaniline supercapacitor to maintain electronic contact between electrodes during the cycle process.
[0033] 4. The present invention adopts aniline derivative copolymer electrode material and hydrogen bond-containing binder to prepare polyaniline-based supercapacitor with excellent cycle performance, which effectively solves the problem of poor cycle life faced by current polyaniline-based supercapacitor devices and provides a solution for improving the cycle life of other conductive polymer devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is the Fourier transform infrared (FTIR) spectrum of PANI, PACM and PACM-SIR electrode materials.
[0035] Figure 2 These are SEM images of PACM (a), AT (b), PMT (c), and PANI (d) materials.
[0036] Figure 3 This is a comparison chart of the three-electrode performance of PACM, AT, PMT, and PANI, and a comparison chart of the electrochemical performance of electrode materials in the three-electrode system; (a) CV curve comparison chart at a scan rate of 50mV / s; (b) CD curve comparison chart at a current density of 1 A / g; (c) specific capacity comparison chart at different current densities.
[0037] Figure 4 The electrochemical performance diagram of PACM electrode in the three-electrode system; (a) CV curve; (b) CD curve; (c) specific capacity at different current densities.
[0038] Figure 5 The electrochemical performance diagram of the PACM-SIR symmetric device; (a) CV curve; (b) CD curve; (c) specific capacity at different current densities; (d) performance diagram of 30,000 cycles at a current density of 5 A / g.
[0039] Figure 6 These are SEM images of the electrode surface of the PACM-SIR symmetric device before cycling (a, b), after 5000 cycles (c, d), and after 30000 cycles (e, f).
[0040] Figure 7These are the electrochemical performance graphs of four symmetrical devices with PANI:SIR:SP:PBI of 70:10:10:10, 70:15:10:5, 70:20:5:5 and PANI:SP:PBI of 70:15:15; (a) CV curve comparison at a scan rate of 50 mV / s; (b) CD curve comparison at a current density of 1 A / g; (c) specific capacity comparison at different current densities; (d) performance comparison for 10,000 cycles at a current density of 5 A / g.
[0041] Figure 8 These are SEM images of PACM-1 (a) and PACM-2 (b).
[0042] Fig. 9 This is a comparison of the three-electrode performance of PACM, PACM-1, and PACM-2, and a comparison of the electrochemical performance of electrode materials in the three-electrode system; (a) CV curve comparison at a scan rate of 50 mV / s; (b) CD curve comparison at a current density of 1 A / g; (c) specific capacity comparison at different current densities.
[0043] Fig.10 The electrochemical performance diagram of the PACM symmetric device; (a) CV curve diagram; (b) CD curve diagram; (c) specific capacity at different current densities compared with the PACM-SIR symmetric device; (d) performance diagram of 30,000 cycles at a current density of 5 A / g compared with the PACM-SIR symmetric device.
[0044] Fig.11 SEM images of the electrode surface of the PACM symmetric device before (a, b) and after (c, d) cycling. DETAILED DESCRIPTION
[0045] The following embodiments related to the present invention are specifically described by way of examples, which are only limited examples used to illustrate the embodiments of the present invention and do not limit the scope of the present invention.
[0046] Embodiment 1:
[0047] 1. Preparation of PACM
[0048] Weigh 170 mg AD and ultrasonically disperse it in a mixed solution of 10 mL ethanol and 10 mL 1 M HCl, marked as solution A; weigh 170 mg mT and ultrasonically disperse it in 15 mL 1 M HCl solution, marked as solution B; weigh 573 mg APS and dissolve it in 20 mL 1 M HCl solution, ultrasonically disperse it, this is solution C; add solution B to solution A in an ice bath environment of 0-5 ° C and stir for 30 minutes, and gradually stir and drop into solution C, the reaction lasts for 4-8 hours, collect the obtained product, wash it with ethanol and deionized water 3-4 times, and collect the product. At the same time, prepare materials according to the mass ratio of AD to mT of 1:0, 2:1, 1:2, and 0:1, respectively, and record them as AT, PACM-1, PACM-2, and PMT.
[0049] 2. Preparation of PANI
[0050] Weigh 340 mg of aniline (An) monomer, add 30 mL of 1M HCl solution and ultrasonically disperse for 20 minutes, marked as solution A; weigh 833 mg of ammonium persulfate (APS), dissolve in 20 mL of 1M HCl solution, marked as solution B; cool solutions A and B in an ice bath at 0-5°C for 30 minutes, add solution B dropwise to solution A under stirring conditions, control the drop rate to one drop every two seconds, and the entire reaction process lasts for 4 hours. Afterwards, the collected solution is centrifuged and washed 3-4 times with a mixed solution of deionized water and ethanol, and the precipitate is collected.
[0051] 3. Preparation of hydrogen bond binder (SIR)
[0052] First, 365 mL of isophorone diisocyanate (IPDI) was measured in a three-necked flask, and 2.5 mL of dimethylformamide (DMF) was added thereto and stirred evenly, which was marked as solution X; 1.45 g of poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (Pluronic P123) was weighed, 5.5 mg of dibutyltin dilaurate (DBTDL) and 10 mL of dimethylformamide (DMF) were added, and stirred evenly, which was marked as solution Y; 390 mg of imidazolidinyl urea (IU) was weighed, 10 mL of dimethylformamide (DMF) was added and stirred evenly, which was marked as solution Z; solution Y was first poured into solution X, the three-necked flask was placed in an oil bath for magnetic stirring, and then the temperature was raised and heated for reaction for 4 h; after the heating was completed, solution Z was added to the three-necked flask, and the reaction was continued by slow heating and stirring for 12 h. After the reaction, 130 mL of isopropyl ether was added to the product to generate a precipitate, which was collected by centrifugation. The precipitation-centrifugation operation was repeated twice, and the collected precipitate was placed in a vacuum drying oven and dried for 24 h to obtain a SIR polymer. 5 mL of NMP solution was added to dissolve the precipitate into a SIR solution of about 50 wt%.
[0053] 4. Electrochemical performance test of three-electrode system
[0054] The PACM, PANI and SIR materials obtained in this example are used as supercapacitor electrode materials as follows: Part of the collected PANI and PACM centrifuge liquid is coated on graphite paper (1×2 cm 2 ) and dried on a heating table at 80℃ for 2h as a working electrode. The electrochemical performance was tested under a three-electrode system. PANI and PACM were used as active materials, SIR was used as a hydrogen bond binder, SP was used as a conductive agent, and PBI was used as a binder. The mass ratio was 70:15:10:5. NMP was used as a solvent to prepare the electrode slurry. The slurry was stirred for more than 14h and coated on a graphite paper (1×2cm 2 ) and dried on a heating table for 10 h as a working electrode.
[0055] 5. Preparation of PBI membrane
[0056] The preparation method of the PBI membrane is as follows: 5 mL of PBI solution is spread evenly on a flat glass plate, slowly shaken to make the liquid level, and dried at 60° C. for 8-12 hours to obtain a PBI membrane with a film thickness of 20 μm.
[0057] 6. Preparation of symmetrical supercapacitors
[0058] Specifically, PACM was used as the active material, SIR as the hydrogen bonding agent, SP as the conductive agent, and PBI as the bonding agent, with a mass ratio of 70:15:10:5. The electrodes were made with N-methylpyrrolidone (NMP) solvent, PBI membrane was used as the diaphragm, and 6MH3PO4 was used as the electrolyte. Two electrodes with equal active material loads and diaphragms were stacked together in a sandwich structure, and the PBI membrane was sandwiched between the active material surfaces of the two electrodes to assemble a symmetrical device. Electrochemical tests were carried out on the symmetrical supercapacitor device.
[0059] Figure 1 Visible in the middle, 1580cm -1 and 1492cm -1 The peak at 810cm is attributed to the vibration of the quinone ring and the benzene ring, which indicates that PANI of the oxidized emerald salt is formed and the vibration intensity of the quinone ring is lower than that of the benzene ring. -1 、1153cm -1 The peaks at 1310 cm-1 can be attributed to the out-of-plane bending vibration of CH -1 The peak at CN stretching vibration, 3445cm -1 Compared with pure PANI, the peak of PACM copolymer has blue shifted, for example, the corresponding C=C stretching vibration peak has shifted from 1492cm -1 Offset to 1472cm -1The blue shift indicates that the conjugated structure of PACM is weakened. -1 The small absorption peak at 1698 cm -1 and 1664 cm -1 The absorption peaks at are C=O and -CONH- vibrations, proving that the carbonyl and amide groups in the SIR were introduced into the electrode material.
[0060] Figure 2 SEM images of PACM, AT, PMT and PANI materials. Figure 2 (a) It can be seen that PACM presents a loose and porous cross-linked network structure. Figure 2 (b) AT presents a dense polymer surface. Figure 2 In (c), the PMT is dispersed and aggregated. Figure 2 (d) shows the clustered coral-like structure of PANI.
[0061] Figure 3 This is a comparison of the electrochemical performances of PACM, AT, PMT and PANI electrode materials in a three-electrode system. Figure 3 (a) The CV curve shows a curve at a scan rate of 50 mV / s. PACM shows a larger curve closed area and a redox peak at a lower potential. Figure 3 (b) and Figure 3 (c) PACM combines AT and PMT to show good rate performance, and the specific capacitance is greatly improved.
[0062] Figure 4 The electrochemical test results of PACM electrode materials in a three-electrode system. Figure 4 (a) CV curves show that the material has excellent pseudocapacitive properties and highly reversible reactions. Figure 4 The CD image in (b) shows a symmetrical charge and discharge curve with no obvious voltage drop, indicating that the electrode material has good conductivity. Figure 4 (c) The specific capacity of the electrode material calculated from the CD curve is 850F / g, 798F / g, 760F / g, 731F / g, and 717F / g at current densities of 1 A / g, 2 A / g, 5 A / g, 10 A / g, and 20 A / g, respectively. At a current density of 20 A / g, the capacity retention rate is 84.3%, indicating good rate performance.
[0063] Figure 5 Figure 2 shows the electrochemical performance of the PACM-SIR symmetric device. Figure 5 (a) The CV curves show that no obvious deformation occurs at different scan rates, indicating that the material has excellent pseudocapacitive properties and reversible redox reactions; Figure 5 The CD curve in (b) shows a charge-discharge platform corresponding to the redox peak of the CV curve, and there is no obvious voltage drop. The specific capacitance is 158.7 F / g at a current density of 1 A / g, indicating that the electrode material has a better specific capacitance and better conductivity. Figure 5 (c) Demonstrates excellent rate performance at different current densities; Figure 5 (d) It shows that the addition of SIR gives the active material excellent cycling performance, with a capacity retention rate of 84.3% after 30,000 cycles at a current density of 5 A / g.
[0064] Figure 6 The SEM images of the PACM-SIR symmetric device before and after 30,000 cycles. It can be clearly seen that as the number of cycles increases, the cracks on the electrode surface gradually move closer together until they disappear, which proves the repair effect of SIR on the electrode surface and maintains the electronic contact between the active material and the electrode sheet. Correspondingly, there is still a high capacity retention rate after 30,000 cycles of charge and discharge.
[0065] Embodiment 2:
[0066] 1. Preparation of hydrogen bond binder (SIR)
[0067] Same as Example 1.
[0068] 2. Preparation of PANI
[0069] Same as Example 1.
[0070] 3. Preparation of symmetrical supercapacitors with hydrogen-bonded binders
[0071] PANI was used as the active material, SIR as the hydrogen bonding agent, SP as the conductive agent, and PBI as the bonding agent. The mass ratios were 70:10:10:10, 70:15:10:5, and 70:20:5:5, respectively, to make the paired devices. The electrodes were made by dissolving in N-methylpyrrolidone (NMP) solvent, using PBI membrane as the diaphragm and 6M H3PO4 as the electrolyte. Two electrodes of equal mass and the diaphragm were stacked together in a sandwich structure, and the middle of the part coated with the electrode material was covered with PBI membrane to assemble into a symmetrical device. The supercapacitor device was electrochemically tested.
[0072] Figure 7 The electrochemical performance diagram of PANI-SIR symmetric devices containing different SIR mass ratios. Figure 7(a) is the CV graph of PANI:SIR:SP:PBI at 70:10:10:10, 70:15:10:5, 70:20:5:5 and PANI:SP:PBI=70:15:15 at a scan rate of 50mV / s. It can be seen that the symmetrical devices at the four ratios have excellent pseudocapacitive characteristics and highly reversible reactions, and the CV curves are similar. Figure 7 (b) The specific capacities at a current density of 1 A / g are 96 F / g, 101 F / g, 92 F / g, and 91 F / g, respectively. From the CD curves, it can be seen that there is no obvious voltage drop for the four materials, and the conductivity of the materials is good. Figure 7 It can be seen in (c) that when excessive SIR is used, the device will have a larger internal resistance, resulting in a decrease in rate performance. The SIR content is taken as 15wt%; Figure 7 (c) (d) are capacity comparison graphs of devices with four different mass ratios after 10,000 cycles at a current density of 5 A / g. When PANI:SIR:SP:PBI is 70:10:10:10, the capacity retention rate is 89%; when PANI:SIR:SP:PBI is 70:15:10:5, the capacity retention rate is 106%; when PANI:SIR:SP:PBI is 70:20:5:5, the capacity retention rate is 90%, while the capacity retention rate of the device with PANI:SP:PBI=70:15:15 is only 79%. Considering the rate and cycle performance, the effect of improving the device cycle stability is more significant when the SIR mass ratio is 15wt%, which is the mass ratio in Example 1.
[0073] Embodiment 3:
[0074] 1. Preparation of PACM
[0075] Same as Example 1.
[0076] 2. Electrochemical performance test of three-electrode system
[0077] The PACM material obtained in this example is used as a supercapacitor electrode material as follows: PACM is used as an active substance, dissolved in deionized water as a solvent, and coated on a graphite paper (1 cm×2 cm). The coating area is 1 cm 2 The working electrode was dried at 80℃ for 20min on a heating table. The electrochemical performance of the electrode material in a three-electrode system was tested with Ag / AgCl as the reference electrode, Pt as the counter electrode, and 1MH2SO4 as the electrolyte.
[0078] Figure 8 (a) and (b) show the SEM images of PACM-1 and PACM-2. When the AD content is too high, the surface structure of the material will be denser. Figure 8(b) The increase in mT content weakens the intermolecular forces between polymers and makes the polymer chains more dispersed.
[0079] Fig. 9 It is a three-electrode chemical performance diagram of different PACMs, PACM-1, and PACM-2. Fig. 9 (a) It can be seen that all three electrode materials have excellent pseudocapacitive characteristic curves and good reversible reactions, and PACM shows a larger closed curve area; Fig. 9 (b) The three CD curves all show symmetrical charge and discharge curves with no obvious voltage drop, which shows the excellent conductivity of the material itself; Fig. 9 In (c), the specific capacities of PACM, PACM-1, and PACM-2 materials at a current density of 1 A / g are 850 F / g, 723 F / g, and 756 F / g, respectively. At a current density of 20 A / g, the rate performances are 84.3%, 84.7%, and 84.6%, respectively. When the rate performances are consistent, PACM exhibits a higher specific capacity, so PACM is taken as the active material of the device, that is, the device active material in Example 1.
[0080] Embodiment 4:
[0081] 1. Preparation of PACM
[0082] Same as Example 1.
[0083] 2. Preparation of PACM-SIR symmetric supercapacitor
[0084] Same as Example 1.
[0085] 3. Preparation of PACM symmetrical supercapacitor
[0086] The electrode slurry was prepared with PACM as active material, SP as conductive agent, PBI as binder, and a mass ratio of 70:15:15. N-methylpyrrolidone (NMP) was used as solvent. PBI membrane was used as separator and 6M H3PO4 was used as electrolyte. Two electrode sheets with the same active material load were assembled with the separator in a stacked structure. The PBI membrane covered one side with active material, and a symmetrical device was assembled. The electrochemical performance of the device was tested.
[0087] Fig.10 (a) CV image of the PACM-SIR symmetric device. The curve does not deform significantly at different scan rates, indicating that the device has excellent pseudocapacitive properties and redox reversibility. Fig.10 The CD curves of (b) and (c) are similar to those of the PACM-SIR device. The capacity at 1 A / g is 142.7 F / g, which is lower than the 158 F / g of the PACM-SIR device, and the rate performance is slightly worse than that of the PACM-SIR device. Fig.10 In (d), the capacity retention rate of the PACM symmetric device is only 72.4% after 30,000 cycles at a current density of 5 A / g, and the cycle stability is obviously worse than that of the device with SIR added.
[0088] Fig.11 : These are SEM images of the PACM electrode before and after cycling. It can be seen that the cracks in the electrode after cycling have expanded significantly, and the electrode surface is not as intact as in Example 1 after cycling.
Claims
1. A method for preparing methyl modified polyaniline, characterized in that: By copolymerizing N-phenyl-p-phenylenediamine and m-methylaniline, methyl functional groups were introduced on the benzene ring to weaken the intermolecular forces of the polymers and regulate the morphology of polyaniline to obtain methyl-modified polyaniline, denoted as PACM.
2. The preparation method according to claim 1, characterized in that The following steps are involved: Step 1: Weigh 100-500 mg of N-phenyl-p-phenylenediamine, add it into a mixed solution of 5-20 mL of ethanol and 10-30 mL of 1M HCl, stir evenly, and disperse by ultrasonication, which is recorded as solution A; Step 2: Weigh 100-500 mg of m-methylaniline, add 1M HCl solution, stir evenly, and disperse by ultrasonication, which is recorded as solution B; Step 3: Weigh 300-1500 mg APS, add 1M HCl solution, stir evenly, and place at 0-5°C for 10-50 min, which is called solution C; Step 4: Pour the solution B obtained in step 2 into the solution A obtained in step 1, disperse by ultrasonic at 0-5°C for 10-30min, and then stir at 0-5°C for 10-40min; Step 5: Slowly drip the solution C obtained in step 3 into the system of step 4 and stir, keep the dripping process for 0.5-2h, and continue to stir and react at 0-5°C for 4-12h; Step 6: The reaction solution obtained in step 5 is washed by centrifugation with a mixed solution of deionized water and ethanol to remove residual acid and organic matter, and the product is collected by freeze drying to obtain methyl-modified polyaniline, which is recorded as PACM.
3. The preparation method according to claim 2, characterized in that: The mass ratio of N-phenyl-p-phenylenediamine to m-methylaniline is 2:1 to 1:
2.
4. A method for constructing a supercapacitor with excellent cycle stability, characterized in that: The PACM or PANI is used as an active material to prepare an electrode slurry and an electrode; PBI is used as a diaphragm and H3PO4 is used as an electrolyte; The two electrode sheets are stacked together with the separator in a sandwich structure with the sides coated with active materials facing each other, and the sides loaded with active materials are respectively attached to the middle PBI membrane to assemble into a symmetrical device.
5. The construction method according to claim 4, characterized in that: The PACM or PANI is used as an active material, and a binder, a conductive agent and a solvent are added to prepare an electrode slurry.
6. The construction method according to claim 5, characterized in that: The adhesive is composed of a hydrogen bond adhesive and polybenzimidazole.
7. The construction method according to claim 6, characterized in that: The mass ratio of active material, hydrogen bond binder, conductive agent and polybenzimidazole is (70%-97%): (1%-15%): (1%-15%): (1%-10%).
8. The construction method according to claim 7, characterized in that: Use graphite paper as current collector to apply electrode slurry to prepare electrodes. The electrode slurry coating area is >1cm 2 .
9. The construction method according to claim 8, characterized in that: The loading mass of active material per electrode is 0.1-5 mg / cm 2 .
10. The construction method according to claim 6, characterized in that: The hydrogen bonding agent is prepared by the following method: (1) Place isophorone diisocyanate in a three-necked flask, add DMF, stir evenly, and mark as solution X; (2) Weigh a certain amount of poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol), add dibutyltin dilaurate and DMF, and stir evenly, which is recorded as solution Y; (3) Weigh a certain amount of imidazolidinyl urea, add DMF and stir evenly, marking it as solution Z; (4) Pour solution Y into solution X and heat to react for 4-8 hours while stirring. After the reaction is completed, add solution Z to the three-necked flask and continue heating and stirring to react for 8-16 hours. (5) After the reaction is completed, isopropyl ether is added to the product to generate a precipitate, and the precipitate is collected by centrifugation. The precipitation-centrifugation operation is repeated twice, and the collected precipitate is placed in a vacuum drying oven to dry, and the precipitate is dissolved with NMP to prepare a hydrogen bonding agent solution with a concentration of 10-50wt%.
Citation Information
Patent Citations
Sulfonic self-doped aniline copolymer with controllable nanometer structure and synthesis method thereof
CN102250345A
Supercapacitor electrode material and preparation method thereof
CN102568644A
Supercapacitor electrode made of nano dendritic polyaniline, and preparation method for supercapacitor electrode
CN105070533A
A lithium ion battery negative electrode active material with high stability and high capacity and a preparation method thereof
CN108987699A
Preparation method of polyaniline long-chain and short-chain composite electrode material and application of polyaniline long-chain and short-chain composite electrode material in construction of wide-voltage supercapacitor
CN113963959A